2017
DOI: 10.1002/brb3.716
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term cost of spouses’ informal support for dependent midlife stroke survivors

Abstract: ObjectivesStroke is a major global disease that requires extensive care and support from society and relatives. The aim of this study was to identify and quantify the long‐term informal support and to estimate the annual cost of informal support provided by spouses to their stroke surviving partner.MethodData were based on the 7‐year follow‐up of the Sahlgrenska Academy Study on Ischemic Stroke. One‐third of the spouses stated that they provided support to their stroke surviving partner. The magnitude of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 31 publications
(41 reference statements)
0
14
0
Order By: Relevance
“…Others have estimated that caregiver assistance might amount to, on average, about 9 to 17 h per week in the first year after stroke. 4,21 In a seven-year follow-up study on 33 caregivers by Persson et al, 22 the time spent providing support to dependent survivors of stroke was subdivided into two components: practical support (35 h per week) and being available (66.5 h per week), suggesting a substantial commitment in addition to the time spent actively providing assistance. We did not use absolute measures of time consumption.…”
Section: Our Results In Relation To Previous Researchmentioning
confidence: 99%
“…Others have estimated that caregiver assistance might amount to, on average, about 9 to 17 h per week in the first year after stroke. 4,21 In a seven-year follow-up study on 33 caregivers by Persson et al, 22 the time spent providing support to dependent survivors of stroke was subdivided into two components: practical support (35 h per week) and being available (66.5 h per week), suggesting a substantial commitment in addition to the time spent actively providing assistance. We did not use absolute measures of time consumption.…”
Section: Our Results In Relation To Previous Researchmentioning
confidence: 99%
“…1 ). The recruited participants and drop-out in the time-diary study have been presented in detail elsewhere [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the quantity of informal support has also been shown to be associated with the stroke survivors’ functional ability [ 14 ], motor and cognitive function [ 15 ] and their stroke-related health problems [ 16 ]. We have recently shown that the spousal support and cost [ 17 ] and QALY-weight [ 18 ] were associated with measures of global function of the stroke survivors. However, it remains to be shown whether there is an association between the stroke survivors’ QALY-weights and the informal support provided by their spouses.…”
Section: Introductionmentioning
confidence: 99%
“…The estimated prevalence of disability after stroke concerns about 40% of the stroke survivors in Sweden (3), which are often long-lasting in the middle-aged group (4). Thus, spouses' often provides long-term support which covers a wide range of activities (5) and can be perceived to bring positive aspects in life (6). However, the informal support can also be demanding and have a negative impact on the spouses wellbeing, leisure activities, social functioning (7,8), and health-related quality of life (9).…”
Section: Introductionmentioning
confidence: 99%